2017
DOI: 10.5489/cuaj.4410
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation options for children and adolescents with cancer

Abstract: Introduction: Cancer in children and adolescents has seen a stark rise in survival rates in the last decades; overall survival in excess of 80% can be reasonably expected for many newly diagnosed patients with malignancies in this age group. Survivorship has unfolded several specific issues faced by these patients, including fertility concerns. Hence, fertility preservation efforts have been discussed and undertaken with increased frequency. Methods: In this article, the authors provide a broad overview of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Previous studies have also shown lower utilisation rates of fertility preservation for female compared with male patients among adolescent and young adult cancer patients (Bann et al., 2015; Benedict et al., 2016; Shnorhavorian et al., 2015). This difference may be explained by the fact that sperm cryopreservation is a safe, reliable and easily available method of fertility preservation in post‐pubertal males (Romao & Lorenzo, 2017; Skinner et al., 2017). In contrast, cryopreservation of oocytes in post‐pubertal females requires hormonal stimulation and therefore delays the start of cancer treatment, which can be prohibitive with most adolescent malignancies (Dittrich et al, 2018; Romao & Lorenzo, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown lower utilisation rates of fertility preservation for female compared with male patients among adolescent and young adult cancer patients (Bann et al., 2015; Benedict et al., 2016; Shnorhavorian et al., 2015). This difference may be explained by the fact that sperm cryopreservation is a safe, reliable and easily available method of fertility preservation in post‐pubertal males (Romao & Lorenzo, 2017; Skinner et al., 2017). In contrast, cryopreservation of oocytes in post‐pubertal females requires hormonal stimulation and therefore delays the start of cancer treatment, which can be prohibitive with most adolescent malignancies (Dittrich et al, 2018; Romao & Lorenzo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fertility preservation should be pursued prior to cancer treatment. Sperm cryopreservation is a well‐established method for post‐pubertal male patients (American Society for Reproductive Medicine et al., 2013; Romao & Lorenzo, 2017; Skinner et al., 2017). Options for females include cryopreservation of unfertilised or fertilised oocytes for post‐pubertal patients, or surgical transposition of the ovaries outside of the pelvic radiation field (American Society for Reproductive Medicine et al., 2013; Dittrich et al, 2018; Lobo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Semen preservation prior to oncotherapy in male cancer patients is advocated for fertility preservation and testicular tissue biopsies are cryopreserved for young pre-pubertal boys [ 63 ]. The field of using cryopreserved testicular tissue for fertility restoration has not developed as impressively as restoring fertility in females from cryopreserved ovarian tissue.…”
Section: Making Sperm In a Dishmentioning
confidence: 99%
“…Finally, guidelines for best practices in counseling are critical to an ethical offer of OTC. Discussion with a fertility specialist should ensure all relevant information is disclosed to promote informed consent and assent [44,48]. Required general anesthesia, minor surgical procedure, need for research participation, experimental nature, and uncertainty of long-term efficacy should be discussed.…”
Section: Discussionmentioning
confidence: 99%